Development of a xanthan gum film for the possible treatment of vaginal infections - Villar-Padilla, Analizet; Del Prado-Audelo, María Luisa; González-Torres, Maykel; Giraldo-Gomez, David M.; Caballero-Florán, Isaac H.; González-Del Carmen, Manuel; Sharifi-Rad, Javad; Figueroa-González, Gabriela; Reyes-Hernández, Octavio D.; Cortés, Hernán; Leyva-Gómez, Gerardo (Cellular and Molecular Biology, 2021)
Bacterial vaginosis is a vaginal infection that affects 60% of women of reproductive age worldwide. It is mainly caused by the bacterium Gardnerella vaginalis and is a factor that increases the probability of getting sexually transmitted diseases. We aimed to develop a new pharmaceutical form for the treatment of vaginal infections. We employed the solving-casting method to fabricate a polymeric film with Xanthan gum, a natural polymer produced by the bacterium Xanthomonas campestris, and metronidazole, one of the most commonly used drugs for vaginal infections. In order to characterize the film, we measured pH, dose uniformity, dissolution profile, and the percentage of swelling. Moreover, we performed a thermogravimetric analysis and scanning electron microscopy. The results demonstrated a pH suitable for vaginal application and uniform distribution of the drug in the film. Also, the formulation exhibited a high percentage of swelling and a slow release of the drug in a simulated vaginal fluid medium. All these attributes indicated that the manufactured film has ideal characteristics to be used and administered vaginally. It could be an excellent alternative to treat bacterial vaginosis and also improve user adherence.